Sistemas de siembra de maiz y frijol en asociación - García, S.; Davis, J. (International Center for Tropical Agriculture, 1980)
Maize and climbing beans as associated crops prevail in the highlands of L.A. in traditional systems with low populations and manual planting (in rows and pocket drilling). Two trials were establislied to compare the systems, testing bean densities from 4- 12 plants/m(2) and 3-12 plants/m(2), with the same maize population and simultaneous planting. Five bean genotypes with different aggressiveness for climbing were tested with one maize genotype (Suwan-1). Row planting was superior in both trials for both crop yields, but the difference was siginificant with a bean density of 8 plants/m(2). This density was considered optimum when the yields of both crops were taken into account. Both the planting system and bean var. had an important effect on the lodging of maize. There was less lodging for pocket drilling than in rows and at a greater bean density due to the better anchoring of the roots. The effect of bean var. on maize yields was closely related to the lodging of the stem caused by bean aggressiveness: max effect with the most aggressive beans (type IV b) and min effect with the weaker climbing beans (type III b). Therefore, maize genotypes for association should have strong stems to resist lodging. (AS)